Gallstone Dislodgement in the Airway during ERCP: A Case Report and Review of the Literature - Hisham Hurreiz; Amira Babikir; Edward Black (Case Reports in Gastrointestinal Medicine)
Endoscopic retrograde cholangiopancreatography (ERCP) is a diagnostic and therapeutic procedure with many studied complications. We are presenting a rare complication of ERCP in choledocholithiasis: gallstone dislodging into the airway upon retrieval. The patient is a 37-year-old female admitted with obstructive jaundice. She was evaluated, and her management plan included a referral for an ERCP to extract the impacted common bile duct stones. Upon retrieval of the gallstone, it fell out the basket and lodged into the airway which was confirmed on bronchoscopy and successfully retrieved. This report describes successful management of a rare but potentially dangerous complication of ERCP to remove impacted CBD stones. The possible complications of delayed removal or inability to remove gallstones from the airway have yet to be studied and reported but are likely to include recurrent chest infections, bronchiectasis, and empyema of the lung.